Vascular Endothelial Growth Factor Regulates the Migration of Oligodendrocyte Precursor Cells - Hayakawa, Kazuhide (Society for Neuroscience, 2011)
Originally identified as an angiogenic factor, vascular endothelial growth factor (VEGF-A) is now known to play multiple roles in the CNS, including the direct regulation of neuronal and astrocytic functions. Here, we ask whether VEGF-A can also have a novel role in white matter by modulating oligodendrocyte precursor cells (OPCs). OPCs were cultured from rat neonatal cortex. Expression of VEGF-receptor2/KDR/Flk-1 was confirmed with Western blot and immunostaining. VEGF-A did not affect proliferation or differentiation in OPC cultures, but VEGF-A promoted OPC migration in a concentration-dependent manner. Consistent with this migration phenotype, VEGF-A-treated OPCs showed reorganization of actin cytoskeleton in leading-edge processes. VEGF-A-induced migration and actin reorganization were inhibited by an anti-Flk-1 receptor-blocking antibody. Mechanistically, VEGF-A induced binding of focal adhesion kinase (FAK) with paxillin. The FAK inhibitor PF573228 reduced VEGF-A-induced OPC migration. VEGF-A signaling also evoked a transient rise in reactive oxygen species (ROS), and OPC migration was increased when antioxidants were removed from the culture media. Our findings demonstrate that VEGF-A can induce OPC migration via an ROS- and FAK-dependent mechanism, and suggest a novel role for VEGF-A in white-matter maintenance and homeostasis.